A systematic review and meta-analysis on the safety and efficacy of premedication prior to elective intubation in neonates - Ilias Chatziioannidis; Georgios N. Katsaras; Abraham Pouliakis; Zoi Arvanitaki; Dimitra Gialamprinou; Georgios Mitsiakos (Hygeia Press di Corridori Marinella, 2024)
Objective: Endotracheal intubation, as an emergent but also as an elective procedure, can be stressful and painful, causing hypoxemia, bradycardia, acidosis or increased intracranial pressure. We aimed to investigate the safety and efficacy of premedication prior to elective intubation in order to contribute to the development of a more standardized strategy. Method: A systematic review and meta-analysis was conducted. The PubMed database was searched using the PICO method and keywords according to MeSH terms were used. Only studies with control groups were included (randomized controlled trials, prospective observational and case-control studies). Results: Our search procedure yielded 722 potentially eligible studies. Finally, 26 studies were included for qualitative and quantitative analysis. Blood pressure during intubation was found lower for neonates that received premedication compared to controls (SMD = -1.27; 95% CI [-2.59; 0.05]; p < 0.01). Heart rate change was found higher in the control group (SMD = -0.26; 95% CI [-1.07; 0.55]; p = 0.54). Intervention groups were found to have higher odds for bradycardia (OR = 1.13; 95% CI [0.79; 1.62]; p = 0.51), and less odds for desaturation compared to control groups (OR = 0.69; 95% CI [0.33; 1.45]; p = 0.33). The odds for adverse events were found 3 times lower in the intervention group, in relation to controls (OR = 0.71; 95% CI [0.55; 0.73]; p = 0.012). Intubation time for the intervention groups was lower than controls (SMD = -0.59; 95% CI [-1.06; -0.11]; p < 0.02). Intubation attempts were found marginally increased in the intervention group (ROM = 1.10; 95% CI [0.79; 1.53]; p = 0.57). No difference was found regarding mortality rate between groups. Conclusion: Most Neonatal Intensive Care Units should consider premedication prior to intubation for vigorously and active term and preterm infants as a safe and efficient procedure that buffers serious physiological responses and assures better procedural conditions.